Prevalence and Risk Factors of Soil-transmitted Helminth Infections in Cattle Breeders in Mlaten Village, East Java - Muhammad Aviv Nur Ridwan; Acivrida Mega Charisma (Universitas Ahmad Dahlan, 2022)
Background: Soil-transmitted helminth infections are diseases caused by the ingestion of infective stages (in the form of eggs, larvae, cysticercoid, and plerocercoid) of worms (nematodes, cestodes, and trematodes) into the human gastrointestinal tract through the fecal-oral route. The risk factors associated with soil-transmitted helminth infections are environmental factors and hygiene factors. These factors are commonly found in agricultural areas. Therefore, we conducted research in Mlaten Village because the majority of the villagers work as cattle breeders. In addition, the surrounding community, especially cattle breeders, experienced excessive diarrhea that was probably caused by a lack of hygiene knowledge, poor sanitation, and low awareness of cattle care and management. This study aims to determine the prevalence and risk factors of soil-transmitted helminth infections in cattle farmers in Mlaten village, Mojokerto, East Java. Methods: This research was conducted using a survey method and cross-sectional study design with 30 cattle farmers as respondents. Human and cow feces were identified using a staining method in the form of 2% eosin. We also used questionnaires to determine the risk factors. The data obtained were presented descriptively and risk factors were analyzed using the chi-square test. Results: The results showed that the habit of cutting nails (OR= 0.083; CI 95%= 0.007-0.950; p<0.05), the habit of washing hands (OR= 0.000; CI 95%= 0.000-0.000; p<0.05), and the habit of washing hands with soap (OR= 0.040; CI 95%= 0.267-18.925; p<0.05) have a significant effect on the incidence of soil-transmitted helminth infections. Conclusion: The prevalence of soil-transmitted helminth infections is significant to personal hygiene risk factors.